Empowering Lives: An Islamic Boarding School's Sustainable Economic - Nursaid, Nursaid; Zamil, Raihan; Labh, Ashor (CV. Bimbingan Belajar Assyfa, 2024)
The background of this study focuses on the challenges faced by Islamic boarding schools in West Java, where there are around 1,300 Islamic boarding schools with more than 100,000 students who need sufficient financial resources to support their educational activities and economic development. This study aims to analyze the effectiveness of the One Pesantren One Product (OPOP) Program in empowering the economy of Islamic boarding schools in the region. The research method used is literature analysis with a qualitative approach, where data is collected from 15 relevant publications published between 2015 and 2023. The data analysis techniques applied include categorizing themes and mapping research results related to the implementation of OPOP. The results of the study indicate that the OPOP program has succeeded in increasing the economic capacity of 60% of Islamic boarding schools through the development of superior products produced by students. In addition, 75% of Islamic boarding schools involved in this program reported a significant increase in income, and 80% of students felt more motivated to learn and become entrepreneurs. The conclusion of this study confirms that the OPOP initiative not only strengthens the economy of Islamic boarding schools, but also improves the quality of education and entrepreneurial skills of students. This study provides recommendations for strengthening policies and ongoing support for the OPOP program so that Islamic boarding schools can be more financially independent and contribute to local economic development.